(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Air gaps layer between clothing and wearer's body plays an important role in heat transfer in protective ensembles. The distribution and size of these air gaps are used to determine thermal performance of the protective clothing, which are dependent not only on garment style and fit but also on all kind of shapes of body motions. In this paper a three dimensional (3D) body scanning technique was used to scan the surface of the nude and the dressed that can measure accurately the distribution and size of air gaps between the human body and clothing. In leg-upright, leg-lifting and leg-withdrawing positions that simulated the human motion of running, the clothing air gaps were scanned and measured respectively. A new method for the measurement of air gaps was used, which can reasonably reflect the size between the fabric and the corresponding test sensor. The results show that clothing air gaps are associated with body motions. The clothing air gaps vary with the different postures. And the degree of knee joint flexion affects the deformation of skin and thus the change of air gaps between skin and clothing. The findings can be used to establish heat transfer model to predict thermal performance of protective clothing in motion.